2009
DOI: 10.1007/s10460-009-9249-y
|View full text |Cite
|
Sign up to set email alerts
|

Standard fare or fairer standards: Feminist reflections on agri-food governance

Abstract: In 2007 new meat inspection regulations standardizing meat production throughout the Province of British Columbia (BC), Canada came into effect moving food for local consumption closer to continentally harmonized production standards. Critics argue that the economic viability of small-scale livestock farmers is threatened. Smallscale women farmers are central to the creation of alternative local agri-food networks in BC. Using gender as an analytically enabling tool this paper argues that public food-safety re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Numerous authors suggest that industrial, "factory" food production systems, which necessitate overuse of antibiotics in animals, are a threat to a safe food supply (Buckley, 2015;McMahon, 2011;Nestle, 2003;Worosz, Knight, Harris, & Conner, 2008). To deal with the increasing threat posed by industrial food production, regulators introduced science-based rules and controls to stem the flow of foodborne disease rather than requiring industry to reduce the scale of food production.…”
Section: Food Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors suggest that industrial, "factory" food production systems, which necessitate overuse of antibiotics in animals, are a threat to a safe food supply (Buckley, 2015;McMahon, 2011;Nestle, 2003;Worosz, Knight, Harris, & Conner, 2008). To deal with the increasing threat posed by industrial food production, regulators introduced science-based rules and controls to stem the flow of foodborne disease rather than requiring industry to reduce the scale of food production.…”
Section: Food Safetymentioning
confidence: 99%
“…The intent of the BC Meat Inspection Regulation change was to standardize meat production in the province, protect public health, and foster confidence in the BC food supply (McMahon, 2011). However, impacts of the new regulations on smallscale producers included higher slaughter costs, lower profit margins, lost revenues, loss of farm status, and reduced livestock production (Johnson, 2008).…”
Section: Conflicts In Food Safety and Local Foodmentioning
confidence: 99%
“…The topic has also been explored under feminist approaches addressing the gender implications of the power and control relationships within the food system (Patel 2012), the impact of public food safety regulations (McMahon 2011) or peasant women's contribution to the evolution of the FSv concept (Desmarais 2007).…”
Section: The Concept Of Fsvmentioning
confidence: 99%
“…Between 2007 and 2010, I studied the impact of new food-safety regulations on local small-scale farmers near where I live in British Columbia (BC), Canada [2]. What I learned about the potential consequences of current trends in food-safety governance and the harmonization of regional or global standards raised troubling questions about the future of vibrant small-scale farms and thriving local economies.…”
Section: Introductionmentioning
confidence: 99%
“…What I learned about the potential consequences of current trends in food-safety governance and the harmonization of regional or global standards raised troubling questions about the future of vibrant small-scale farms and thriving local economies. While much recent research literature now stresses the need to recognize the connections between human and environmental health [3][4][5][6], my research showed me how easily efforts for greater local food security 2 and ecological and resilient agriculture can be undermined in the name of food-safety. The context for changes in BC's food-safety governance is important.…”
Section: Introductionmentioning
confidence: 99%